Resin composition for secondary battery electrode and use thereof
Patent Information
- Application Number
- JP2024013442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-23
- Filing Date
- 2024-01-31
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2044-01-31
AI Technical Summary
【0017】 本発明の実施形態によれば、カーボンナノチューブの分散性とフッ素樹脂の溶解性を両立し、高い分散性および経時安定性を有する二次電池電極用樹脂組成物を提供することが可能である。また、本発明の他の実施形態によれば、活物質と混合した後も、カーボンナノチューブの分散性に優れるため、カーボンナノチューブの凝集物やフッ素樹脂の継粉が発生しにくい二次電池電極用合材スラリーを提供することが可能である。本発明のさらに他の実施形態によれば、高出力、高容量、高寿命な二次電池を提供することができる。
Smart Images

Figure 2025003280000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for a secondary battery electrode, more specifically, to a resin composition for a secondary battery electrode, a composite slurry for a secondary battery electrode containing the resin composition for a secondary battery electrode and an active material, an electrode film formed from the composite slurry, and a secondary battery including the electrode film. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.
[0003] The electrode of a secondary battery is prepared by applying a composite slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, etc., to a current collector. A conductive material dispersion liquid in which a conductive material is dispersed in a dispersion medium is prepared, and an active material and a binder resin are added to the conductive material dispersion liquid to prepare a composite slurry, so that the conductive material is uniformly dispersed and contained in the electrode film, and the conductivity of the electrode film can be improved. The conductive material dispersion liquid can be used in common with various composite slurries, but the composite slurry is prepared by adjusting the type of active material, the mixing ratio of each component, etc. according to the specifications of the battery or electrode. Therefore, it is desired that the dispersibility and fluidity are maintained even during storage of the conductive material dispersion liquid before adding the active material. Furthermore, if the conductive material dispersion liquid can be stably stored in the state of a resin composition in which a binder resin is added, the work of preparing the composite slurry can be simplified.
[0004] As the conductive material, carbon black, graphene, fine carbon materials, etc. are used, but in order to further improve the conductivity and improve the capacity of the battery, the use of carbon nanotubes, which are a type of fine carbon fiber, has been considered. For example, by adding carbon nanotubes to the positive electrode, the conductivity of the electrode film can be improved and the electrode resistance can be reduced. Among them, multi-walled carbon nanotubes with an outer diameter of several nm to several tens of nm are relatively inexpensive and are being put to practical use. If carbon nanotubes with a small average outer diameter and a large fiber length are used, a conductive network can be efficiently formed even in a small amount, and the capacity of the secondary battery can be increased. On the other hand, carbon nanotubes with these characteristics have a strong cohesive force, making it difficult to further improve the dispersibility of the carbon nanotube dispersion.
[0005] Patent Document 1 discloses a method for producing a composition for forming a positive electrode, which is characterized by first dispersing a conductive material, and then sequentially adding and dispersing a powdered binder resin and a positive electrode active material. Patent Document 1 shows that the use of a powdered binder resin prevents the conventional binder resin from surrounding the positive electrode active material and the conductive material and preventing contact with the electrolyte, thereby reducing the battery characteristics, and that the disclosed production method increases the dispersibility of the composition for forming a positive electrode, reduces the internal resistance of the battery, improves the output characteristics, and improves the adhesive strength throughout the electrode.
[0006] Patent Document 2 and Patent Document 3 disclose a resin composition that further contains a fluororesin as a binder resin in a conductive material dispersion liquid that contains a conductive material containing carbon nanotubes, a dispersant, and a dispersion medium. Patent Document 2 discloses that by further adding a binder resin to a carbon nanotube dispersion liquid in which the dispersion state is appropriately controlled so that the product (X×Y) of the complex modulus X (Pa) and the phase angle Y (°) at 25° C. and 1 Hz as measured by dynamic viscoelasticity measurement is within a predetermined range, it is possible to maintain fluidity even in a state in which the binder resin has been added to the carbon nanotube dispersion liquid, and by forming an electrode film using this resin composition, it is possible to develop a fluororesin that is developed in the electrode film. Patent Document 3 also shows that by setting the product (X×Y) of the complex modulus X (Pa) and the phase angle Y (°) at 25° C. and 1 Hz in a dynamic viscoelasticity measurement of a resin composition containing carbon nanotubes, a dispersant, a fluororesin, and a dispersion medium within a predetermined range, fluidity is maintained even in a state containing carbon nanotubes and a fluororesin, and that by forming an electrode film using this resin composition, a developed conductive network is formed in the electrode film. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2018-503946 [Patent Document 2] Patent No. 7107413 [Patent Document 3] Patent No. 7109632 Summary of the Invention [Problem to be solved by the invention]
[0008] There is a demand for high concentrations of resin compositions, more specifically, high concentrations of carbon nanotubes and fluororesins, due to delivery costs, supply risks of dispersion medium, freedom of composite slurry design, etc. However, resin compositions containing these at high concentrations have problems such as poor flowability, storage stability, and mixing stability when an active material is added.
[0009] In addition, if shear stress is applied when the active material and the resin composition are mixed in the manufacturing process of the composite slurry, a sudden change in the distribution of the dispersion solvent and a shock due to the influence of the electrons on the surface of the active material may occur, and aggregates of carbon nanotubes may be generated. This is particularly likely to occur when the carbon nanotube concentration is higher than a certain level or when the fluororesin content is high.
[0010] In the method of preparing a resin composition, the solubility of the fluororesin in a solid state is insufficient in the method shown in Patent Document 1, and when a fluororesin is added at a certain concentration or above, or when a fluororesin with a large molecular weight is added, the fluidity of the resin composition drops sharply, and the fluororesin particles tend to clump together, making it difficult to obtain a composite slurry that is stable over time when mixed with an active material. In addition, there is room for improvement in the adhesion between the resulting electrode film and the current collector. Patent Documents 2 and 3 disclose techniques for forming a developed conductive network in an electrode film by controlling the dispersibility and viscosity characteristics of a resin composition containing a fluororesin by using the complex modulus and phase angle, but the dissolution conditions and uniformity of the fluororesin are not fully investigated.
[0011] The present inventors conducted a detailed comparative study of the minute differences in the dispersion state of resin compositions containing fluororesin as a binder resin, and found that when fibrous carbon nanotubes are used as a conductive material, the particle size distribution and viscosity, which have often been used as indicators of the dispersion state of conventional resin compositions, may have different characteristics when used in secondary batteries even if the same measured values are used, and the dispersion state of carbon nanotubes and the dissolution state of fluororesin are not accurately captured. For example, in the case of particle size distribution, fibrous non-spherical particles are assumed to be spherical when calculated, so that deviation from the actual situation is likely to occur. In the case of viscosity, it is generally said that the better the dispersion state of the conductive material, the lower the viscosity, but when the conductive material is fibrous and easily entangled, even if the conductive material is in a uniform and stable state in the dispersion medium, the elasticity becomes strong due to the structural viscosity of the conductive material itself. In addition, when the fibers are broken, the viscosity changes due to two factors, disaggregation and breakage, so it is difficult to accurately express the state of the conductive material by viscosity alone. If the carbon nanotube fibers are broken, the contact resistance between the carbon nanotubes increases, making it difficult to form a well-developed conductive network in the electrode. Therefore, it is effective to avoid breaking the fibers as much as possible and to disperse them uniformly. Since the viscoelasticity of the resin composition changes significantly even during the process of adding, the change in the dispersion state of the conductive material present in the resin composition or the dissolved state of the fluororesin cannot be explained by the viscosity value alone.
[0012] Thus, in the conventionally known carbon nanotube dispersion liquid, the change in the dispersion state of the carbon nanotubes caused by the addition of the fluororesin cannot be fully captured, and the dispersibility and fluidity of the resin composition may be reduced. On the other hand, when the fluororesin is added after the carbon nanotube dispersion liquid is prepared, the dispersion liquid turns black due to the carbon nanotubes, so it is not easy to confirm the solubility of the fluororesin.
[0013] That is, the problem to be solved by the present invention is to provide a resin composition for secondary battery electrodes having high dispersibility and long-term stability, and to provide a composite slurry for secondary battery electrodes having good dispersibility of carbon nanotubes even when mixed with an active material. More specifically, the problem to be solved by the present invention is to provide an electrode film having excellent adhesion to a current collector, and a secondary battery having high output, high capacity, and long life, and an electrode film used therefor. [Means for solving the problem]
[0014] As a result of intensive research by the present inventors aimed at solving the above-mentioned problems, it has been found that the regression line of formula (I) or formula (II) obtained by using a resin composition has a coefficient of determination R 2 It has been found that a resin composition having a slope a and an intercept b of 0.85 or more and satisfying specific ranges maintains the dispersibility and fluidity of the resin composition even over time, and that forming an electrode film using this resin composition can form a well-developed conductive network in the electrode film. This makes it possible to provide an electrode film with excellent adhesion to a current collector, and a secondary battery with high output, high capacity, and long life.
[0015] In other words, by carefully controlling the dispersion state of the carbon nanotubes and the dissolution state of the fluororesin, which is the binder resin, it is possible to obtain a resin composition that is less likely to produce carbon nanotube agglomerates or fluorine resin splices, and it is also possible to create a composite slurry that has good stability over time even when mixed with an active material. Furthermore, this makes it possible to exert the excellent effect of suppressing the occurrence of carbon nanotube agglomerates and splices of fluororesin, even when the carbon nanotube concentration is high or when the fluororesin is contained at a high concentration.
[0016] That is, the present invention includes the following embodiments, but the embodiments of the present invention are not limited to the following. [1] A dispersion medium comprising carbon nanotubes, a dispersant, a fluororesin, and a non-aqueous dispersion medium; The coefficient of determination R of the regression line represented by the following formula (I) 2 I is 0.85 or more, and the slope a I is 2≦a I <20 and y-intercept b I is -5≦b I <10. y=a I x+b I Formula (I) (Formula (I) is A regression line expressed by the least squares method from a scatter diagram in which x is plotted on the horizontal axis and y is plotted on the vertical axis, the measurement being performed using at least three of the resin compositions for secondary battery electrodes after static storage at T° C. for i days, x is 25°C, shear rate 1.0 s -1 Shear viscosity η T-i Nature of (Pa·s) Logarithm (ln(η T-i )) and y is the complex modulus G at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa), i is the number of days that have passed since the resin composition for a secondary battery electrode was stored stationary, assuming that the production date of the resin composition for a secondary battery electrode is 0, and is 7, 14, or 21; T is the static storage temperature of the resin composition for secondary battery electrodes, which is 25, 40, or 60. [2] A dispersion medium comprising carbon nanotubes, a dispersant, a fluororesin, and a non-aqueous dispersion medium; The coefficient of determination R of the regression line represented by the following formula (II) 2 II is 0.85 or more, and the slope a II is 2≦a II <20 and y-intercept b II is -5≦b II <10. y=a II x+b II ...Formula (II) (Formula (II) is a regression line expressed by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, the measurements being made using at least two of the resin composition for a secondary battery electrode on the day of manufacture and the resin composition for a secondary battery electrode after static storage at T°C for i days; x is 25°C, shear rate 1.0 s -1 Shear viscosity η T-i (Pa s) natural logarithm (ln(η T-i )) and y is the complex modulus G at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa), i is the number of days that have passed since the resin composition for a secondary battery electrode was stored stationary, assuming that the production date of the resin composition for a secondary battery electrode is 0, and is either 7, 14, or 21; T is the static storage temperature of the resin composition for secondary battery electrodes, which is 25, 40, or 60. [3] After being stored at T°C for i days, the resin composition for secondary battery electrodes has <1-1> Resin compositions for secondary battery electrodes after static storage at 25°C for 7, 14, and 21 days, <1-2> A resin composition for a secondary battery electrode after being stored at 40°C for 7, 14, and 21 days, or <1-3> Resin compositions for secondary battery electrodes after static storage at 60°C for 7, 14, and 21 days; The resin composition for a secondary battery electrode according to [1] or [2], [4] After being stored at T°C for i days, the resin composition for secondary battery electrodes has <2-1> T is 25 or 40, At least one of the resin compositions for secondary battery electrodes after static storage at 25° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, <2―2>T is 25 or 60, At least one of a resin composition for a secondary battery electrode after static storage at 25° C. for 7, 14, and 21 days, and at least one of a resin composition for a secondary battery electrode after static storage at 60° C. for 7, 14, and 21 days, or <2-3> T is 40 or 60, At least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 60° C. for 7, 14, and 21 days, The resin composition for a secondary battery electrode according to [1] or [2], [5] After being stored at T°C for i days, the resin composition for secondary battery electrodes has <3> The resin composition for a secondary battery electrode according to [1] or [2], comprising at least one of the resin compositions for a secondary battery electrode after static storage at 25° C. for 7, 14, and 21 days, at least one of the resin compositions for a secondary battery electrode after static storage at 40° C. for 7, 14, and 21 days, and at least one of the resin compositions for a secondary battery electrode after static storage at 60° C. for 7, 14, and 21 days. [6] The resin composition for a secondary battery electrode according to any one of [1] to [5], characterized in that the fluororesin has a weight average molecular weight of 100,000 or more and 2,000,000 or less. [7] A composite slurry comprising the resin composition for a secondary battery electrode according to any one of [1] to [6] and an active material. [8] An electrode film formed from the composite slurry according to [7]. [9] A secondary battery having a positive electrode and a negative electrode, A secondary battery, wherein at least one of a positive electrode and a negative electrode has the electrode film according to [8]. Effect of the Invention
[0017] According to an embodiment of the present invention, it is possible to provide a resin composition for secondary battery electrodes that has both the dispersibility of carbon nanotubes and the solubility of fluororesin, and has high dispersibility and stability over time. According to another embodiment of the present invention, it is possible to provide a composite slurry for secondary battery electrodes that has excellent dispersibility of carbon nanotubes even after mixing with an active material, and therefore is less likely to generate aggregates of carbon nanotubes or splices of fluororesin. According to yet another embodiment of the present invention, it is possible to provide a secondary battery with high output, high capacity, and long life. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 shows an example of a scatter plot in which the natural logarithm (ln(η)) of shear viscosity η (Pa s) and complex modulus G* (Pa) measured using resin compositions of Examples and Comparative Examples, and a regression line expressed from the scatter plot by the least squares method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the resin composition for secondary battery electrodes, the composite slurry for secondary battery electrodes, the electrode film, and the secondary battery, as well as the manufacturing method thereof, which are embodiments of the present invention, will be described in detail. The present invention is not limited to the following embodiments, and the present invention also includes embodiments that are implemented within the scope of the present invention. In addition, in this specification, a numerical range specified using "~" includes the numerical values written before and after "~" as the lower and upper limit ranges.
[0020] In this specification, carbon nanotubes may be referred to as "CNT" and N-methyl-2-pyrrolidone as "NMP". In this specification, carbon nanotube dispersions may be referred to as "CNT dispersions", "conductive material dispersions", or simply "dispersions". In addition, non-aqueous dispersion mediums may be referred to as "dispersion mediums", resin compositions for secondary battery electrodes as "resin compositions", and non-aqueous electrolyte secondary batteries as "secondary batteries". Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a mixture of two or more types. The numerical values specified in this specification are values determined by the methods disclosed in the embodiments or examples.
[0021] ≪Resin composition for secondary battery electrodes≫ A resin composition for a secondary battery electrode according to one embodiment of the present invention comprises carbon nanotubes, a dispersant, a fluororesin, and a non-aqueous dispersion medium, The coefficient of determination R of the regression line represented by the following formula (I) 2 I is 0.85 or more, and the slope a I is 2≦a I <20 and y-intercept b I is -5≦b I b < 10, the resin composition for a secondary battery electrode. y=a I x+b I Formula (I) (Formula (I) is A regression line expressed by the least squares method from a scatter diagram in which x is plotted on the horizontal axis and y is plotted on the vertical axis, the measurement being performed using at least three of the resin compositions for secondary battery electrodes after static storage at T° C. for i days, x is 25°C, shear rate 1.0 s -1 Shear viscosity η T-i (Pa s) natural logarithm (ln(η T-i )) and y is the complex modulus G at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa), i is the number of days that have passed since the resin composition for a secondary battery electrode was stored stationary, assuming that the production date of the resin composition for a secondary battery electrode is 0, and is 7, 14, or 21; T is the static storage temperature of the resin composition for secondary battery electrodes, which is 25, 40, or 60.
[0022] A resin composition for a secondary battery electrode according to one embodiment of the present invention includes carbon nanotubes, a dispersant, a fluororesin, and a non-aqueous dispersion medium, The coefficient of determination R of the regression line represented by the following formula (II) 2 II is 0.85 or more, and the slope a II is 2≦a II <20 and y-intercept b II is -5≦b II <10. y=a II x+b II ...Formula (II) (Formula (II) is a regression line expressed by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, the measurements being made using at least two of the resin composition for a secondary battery electrode on the day of manufacture and the resin composition for a secondary battery electrode after static storage at T°C for i days; x is 25°C, shear rate 1.0 s -1 Shear viscosity η T-i (Pa s) natural logarithm (ln(η T-i )) and y is the complex modulus G at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa), i is the number of days that have passed since the resin composition for a secondary battery electrode was stored stationary, assuming that the production date of the resin composition for a secondary battery electrode is 0, and is either 7, 14, or 21; T is the static storage temperature of the resin composition for secondary battery electrodes, which is 25, 40, or 60.
[0023] The resin composition for secondary battery electrodes means a state before the active material is added. In this respect, the resin composition for secondary battery electrodes is distinguished from a composite material slurry containing an active material. That is, the resin composition for secondary battery electrodes does not substantially contain an active material. This is a concept excluding a state in which an active material is intentionally added to the resin composition for secondary battery electrodes, and the active material may be 1 mass % or less, 0.5 mass % or less, or 0.1 mass % or less, or may be 0 mass %, based on the total mass of the resin composition for secondary battery electrodes. The active material will be described later.
[0024] In the present invention, the regression line formula (I) or formula (II) has a coefficient of determination R 2 The resin composition has a slope a of 0.85 or more and a y-intercept b that falls within a specific range, and thus the dispersion stability of the carbon nanotubes in the resin composition containing the fluororesin is excellent. As a result, the dispersibility and fluidity of the resin composition are maintained even over time, and a conductive network developed in the electrode film can be formed by forming an electrode film using this resin composition. This allows the electrode film to have excellent adhesion to the current collector, and further allows the secondary battery to have high output, high capacity, and long life.
[0025] Such a resin composition satisfying formula (I) or formula (II) can be obtained by appropriately controlling the types and contents of CNTs, dispersant, binder resin, and non-aqueous dispersion medium, as well as the manufacturing conditions for mixing and dispersing them. In particular, it is effective to control the mixing conditions (addition rate, temperature, etc.) when adding a fluororesin to a CNT dispersion liquid described later. By doing so, even a black resin composition containing carbon nanotubes in which the solubility of the fluororesin cannot be confirmed visually can have excellent solubility of the fluororesin.
[0026] In this way, the dispersibility of CNTs in a resin composition can be evaluated by the shear viscosity and the complex modulus in dynamic viscoelasticity measurements. By adjusting the composition of the resin composition and the preparation method so that the shear viscosity and complex modulus of the resin composition under specific conditions satisfy the above relationship, it is possible to maintain high dispersibility and fluidity even in a resin composition that contains high concentrations of CNTs or fluororesin.
[0027] In particular, the regression lines of both formulas (I) and (II) have a coefficient of determination R 2 From the viewpoint of excellent stability of the carbon nanotubes and excellent characteristics of the secondary battery, a resin composition having a slope a and a y-intercept b of 0.85 or more and satisfying specific ranges is preferred.
[0028] The regression line expressed by the least squares method from a scatter plot with x on the horizontal axis and y on the vertical axis is expressed by the following formula, where the slope is a and the y-intercept is b. y=ax+b... The coefficient of determination is R 2 Let us assume that.
[0029] The regression line of the present invention can be obtained by measuring at least three resin compositions after static storage at T°C for i days, or at least two resin compositions: a resin composition on the day of manufacture and a resin composition after static storage at T°C for i days. In formula (I), the coefficient of determination is R 2 I , the slope is a I , y-intercept is b I In formula (II), the coefficient of determination is R 2 II , the slope is a II , y-intercept is b II This is expressed as: The coefficient of determination R 2 , the slope a, and the y-intercept b. In formula (I), the coefficient of determination R 2 I , slope a I , y-intercept b I In formula (II), the coefficient of determination R 2 II , slope a II , y-intercept b IIThis refers to:
[0030] Coefficient of determination R 2 If the ratio is less than 0.85, the resin composition will contain "particles" (aggregates of fluororesin) and fine undissolved matter, which will cause aggregation and gelation of the CNTs and fluororesin over time, resulting in a decrease in the adhesion of the electrode film and a decrease in battery performance. R 2 is preferably 0.90 or more, and more preferably 0.95 or more.
[0031] The slope a is 2≦a<20. It is preferably 5 or more, and more preferably 7 or more. It is also preferably less than 15, and more preferably less than 14. If the slope a is less than 2, the fluororesin in the resin composition will be in a non-uniform state, causing a decrease in the adhesion of the electrode film. In addition, there is a risk of battery performance deteriorating. If the slope a is 20 or more, there will be "particles" that are aggregates of CNTs or fluororesin, and fine undissolved matter in the resin composition, which may cause gelation, increase electrode resistance, or decrease battery performance.
[0032] The y-intercept b is -5≦b<10, preferably -3 or more, more preferably 0 or more. Also, it is preferably less than 8, more preferably less than 6. When the y-intercept b is less than -5, the fluororesin in the resin composition is in a non-uniform state, which reduces the adhesion of the electrode film. In addition, there is a risk of battery performance deteriorating. When the y-intercept b is 10 or more, the resin composition contains CNT aggregates, fluororesin aggregates ("powder"), and fine undissolved matter, which may cause gelation, increase electrode resistance, or reduce battery performance.
[0033] By controlling the dispersion state of the CNTs and the dissolution state of the fluororesin binder resin to produce a resin composition in which formula (I) or (II) satisfies specific conditions, it is possible to simultaneously achieve the dispersion stability, stability over time, adhesion between the electrode film and the current collector, and battery characteristics of the resin composition.
[0034] Formula (I) or (II) can be determined by measuring the resin composition for a secondary battery electrode on the day of manufacture and the resin composition for a secondary battery electrode after being stored stationary at T° C. for i days. i is the number of days that have passed since static storage, assuming that the production date of the resin composition is day 0, and is 7, 14, or 21. The resin composition on the production date corresponds to i=0. T is the static storage temperature, which is 25, 40, or 60. That is, for example, T=25, i=7 refers to a resin composition that was stored stationary at 25° C. for 7 days from the date of production.
[0035] Formula (I) can be expressed by measuring the shear viscosity and complex modulus of a resin composition after static storage for 7, 14, or 21 days from the date of production at a temperature of 25, 40, or 60°C, and then determining a regression line from at least three points obtained by plotting x and y. For formula (II), a regression line can be obtained from at least three points: one point obtained by plotting x and y, which are obtained by measuring the shear viscosity and complex modulus using the resin composition on the day of manufacture, and two points obtained by plotting x and y, which are obtained by measuring the shear viscosity and complex modulus using the resin composition after static storage for 7, 14, or 21 days from the day of manufacture and at a temperature of 25, 40, or 60°C. The regression line of formula (II) may be determined by measuring at least three resin compositions, namely, a resin composition on the day of production and a resin composition for a secondary battery electrode after being stored stationary at T° C. for i days.
[0036] In other words, the resin composition for secondary battery electrodes after static storage at T°C for i days refers to nine resin compositions: resin compositions stored statically at 25°C for 7 days, 14 days, and 21 days, resin compositions stored statically at 40°C for 7 days, 14 days, and 21 days, and resin compositions stored statically at 60°C for 7 days, 14 days, and 21 days. Measurement can be performed using any one of these resin compositions to determine the regression line.
[0037] In addition, the resin composition for secondary battery electrodes after static storage at T° C. for i days was as follows: <1-1> Resin compositions for secondary battery electrodes after static storage at 25°C for 7, 14, and 21 days, <1-2> A resin composition for a secondary battery electrode after being stored at 40°C for 7, 14, and 21 days, or <1-3> Resin compositions for secondary battery electrodes after static storage at 60°C for 7, 14, and 21 days; Either of the following can be used.
[0038] In another embodiment, the resin composition for a secondary battery electrode after static storage at T° C. for i days has a <2-1>T of 25 or 40, At least one of the resin compositions for secondary battery electrodes after static storage at 25° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, <2―2>T is 25 or 60, At least one of a resin composition for a secondary battery electrode after static storage at 25° C. for 7, 14, and 21 days, and at least one of a resin composition for a secondary battery electrode after static storage at 60° C. for 7, 14, and 21 days, or <2-3> T is 40 or 60, At least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 60° C. for 7, 14, and 21 days, Either of the following can be used.
[0039] In another embodiment, the resin composition for a secondary battery electrode after static storage at T ° C. for i days is <3> At least one of the resin compositions for secondary battery electrodes after static storage at 25° C. for 7, 14, and 21 days, at least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 60° C. for 7, 14, and 21 days, can be used.
[0040] The above <1-1~3>, <2-1~3>, and <3> The coefficient of determination R of the regression line represented by the formula (I) is determined by measuring using any one of the resin compositions. 2 I is 0.85 or more, and the slope a I is 2≦a<20 and y-intercept b I It is preferable that b is −5≦b<10.
[0041] In addition, the resin composition on the day of manufacture and the above <1-1 to 3>, <2-1 to 3>, and <3> The coefficient of determination R of the regression line represented by the formula (II) is determined by measuring using any one of the resin compositions. 2 II is 0.85 or more, and the slope a II is 2≦a<20 and y-intercept b II It is preferable that b is −5≦b<10.
[0042] x is 25°C, shear rate 1.0 s -1 Shear viscosity η T-i (Pa s) natural logarithm (ln(η T-i )). Here, the shear viscosity η T-i (Pa s) represents the shear viscosity η (Pa s) measured using a resin composition after static storage at T℃ for i days. Note that the shear viscosity η (Pa s) measured using a resin composition on the day of manufacture is represented as shear viscosity η0 (Pa s).
[0043] y is the complex modulus G at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa). Here, the complex modulus G * T-i (Pa) is the complex modulus G measured using a resin composition after standing for T℃i days. * (Pa). The complex elastic modulus G measured using the resin composition on the day of manufacture * (Pa) is the complex modulus of elasticity G * This is expressed as 0(Pa).
[0044] The shear viscosity η (Pa s) of the resin composition is 25°C and a shear rate of 1.0 s-1 The complex modulus G * (Pa) is a measured value at 25°C and a frequency of 1 Hz. For details, it can be measured by the method described in the Examples. The shear rate of the resin composition tends to be smaller as the dispersibility of the CNT is better, but when the fiber length of the CNT is large, even if the CNT is uniformly and stably dissolved in the medium, the value itself may be high due to the structural viscosity of the CNT itself. In addition to the dispersion state of the CNT, it also changes due to the entanglement of the CNT, dispersant, fluororesin, and other resin components, or the influence of their intermolecular forces. In particular, the viscosity value changes significantly depending on the solubility of the fluororesin, and if the fluororesin is in a uniform state in the medium, the viscosity value will be a high value.
[0045] The complex modulus indicates the hardness of the resin composition, and tends to be smaller as the CNT dispersibility is better and as the resin composition has a lower viscosity. However, similar to the shear viscosity, when the CNT itself has structural viscosity, the complex modulus may be a high value even if the CNT is uniformly and stably dissolved in the medium. In addition to the dispersion state of the CNT, it also changes due to the entanglement of the CNT, dispersant, fluororesin, and other resin components, or the influence of their intermolecular forces.
[0046] Resin composition temperature: 25°C; shear rate: 1.0 s -1 The shear viscosity η (Pa s) in is preferably 0.05 Pa s or more, more preferably 0.1 Pa s or more, and even more preferably 0.5 Pa s or more. By having a shear viscosity of 0.05 Pa s or more, the CNTs are sufficiently disintegrated and a resin composition in which the fluororesin is uniformly dissolved can be obtained, resulting in high composite adhesion and excellent battery performance. The shear viscosity is preferably 100 Pa s or less, more preferably 80 Pa s or less, and even more preferably 60 Pa s or less. A shear viscosity of 100 Pa s or less is preferable because it allows for the production of a resin composition in which the CNTs are stably dispersed without any aggregates of the CNTs or fluororesin, thereby resulting in better battery performance.
[0047] Complex modulus of elasticity G of resin composition at 25℃ and 1Hz * (Pa) is preferably at least 1 Pa, more preferably at least 3 Pa, and even more preferably at least 5 Pa. When the complex modulus is at least 1 Pa, the CNTs are sufficiently unraveled, and a resin composition in which the fluororesin is uniformly dissolved can be obtained. The complex modulus is preferably 100 Pa or less, more preferably 80 Pa or less, and even more preferably 50 Pa or less. A complex modulus of 100 Pa or less is preferable because it allows for the production of a resin composition free of aggregates of CNTs or fluororesin and in which CNTs are stably dispersed, thereby resulting in better battery performance.
[0048] The dispersibility of CNT in the resin composition can also be evaluated by the filtration rate of the resin composition. More specifically, the resin composition can be evaluated by diluting it 5 times with a non-aqueous dispersion medium and measuring the time it takes for the entire amount to pass through when the resin composition is filtered under reduced pressure. This is thought to be because, when a small amount of aggregates derived from CNTs or fluororesin are present in the resin composition, the aggregates cannot pass through the filtration filter or the filtration rate is slow. In addition, when the dispersion state of the resin composition is unstable, dispersion shock is likely to occur when the resin composition is diluted with a non-aqueous dispersion medium, and the aggregates are significantly confirmed, so similarly, the filtration filter cannot be passed through or the filtration rate is slow. For the above reasons, the filtration rate can be used as an index for evaluating the dispersion state of CNT in the resin composition, the solubility of the fluororesin, and the fluidity of the resin composition. More specifically, it can be measured by the method described in the examples.
[0049] The fluidity and dispersion stability of the resin composition can be evaluated by checking the storage stability. More specifically, the initial viscosity of the resin composition and the viscosity after the resin composition is left to stand at 40°C for 7 days are measured, and the viscosity after the resin composition is left to stand at 40°C for 7 days is measured, and the viscosity can be evaluated based on the rate of change in the viscosity after the resin composition is left to stand at 40°C for 7 days relative to the initial viscosity. Even if the CNTs are well dispersed at the initial stage, if aggregates derived from the CNTs or fluororesin are present in the resin composition, the CNTs may aggregate around the aggregates during the storage period, causing poor dispersion. By evaluating under these conditions, the dispersion state of the CNTs in the resin composition and the solubility of the fluororesin can be evaluated, taking into account changes over time. More specifically, the viscosity can be measured by the method described in the Examples.
[0050] The average fiber length of the CNTs in the resin composition is preferably 0.1 μm or more, more preferably 0.2 μm or more, and more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the CNTs in the resin composition is calculated by observing a sample obtained by diluting the resin composition 50 times with a non-aqueous dispersion medium such as NMP, dropping it onto a substrate, and drying the sample with a scanning electron microscope, and selecting any 300 CNTs from the observation photograph, measuring the fiber length of each CNT, and averaging the measured fiber length.
[0051] The content of CNT in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the mass of the resin composition (100% by mass). Also, it is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 8% by mass or less. The above content can suppress the occurrence of precipitation and gelation, while allowing the CNT to exist well and stably. It is more preferably 0.1% by mass or more and 20% by mass or less, and even more preferably 0.5% by mass or more and 10% by mass or less.
[0052] In the resin composition, the mass ratio of the dispersant to the CNT (dispersant / CNT) is preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.1 or more. Also, it is preferably 2 or less, more preferably 1 or less, and even more preferably 0.5 or less. By setting it in the above range, the dispersion stability of the CNT can be further improved. It is more preferably 0.01 or more and 2 or less, and even more preferably 0.1 or more and 1 or less.
[0053] The content of the dispersant in the resin composition is preferably 0.1% by mass or more and 5% by mass or less, and more preferably 0.4% by mass or more and 1% by mass or less, based on the mass of the resin composition (100% by mass).
[0054] The content of the fluororesin in the resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, and particularly preferably 3.1% by mass or more, based on the mass of the resin composition (100% by mass). The content of the fluororesin in the above range is preferable because sufficient adhesion of the electrode can be obtained. The resin composition of the present invention can be stably used even if the content is 3.5% by mass or more. The content of the fluororesin in the resin composition is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the mass of the resin composition. The content of the fluororesin in the above range makes it easier to dissolve the entire amount of the fluororesin in the resin composition, suppresses the occurrence of aggregation and gelation, and prevents a decrease in the capacity characteristics of the battery, which is preferable.
[0055] When the resin composition contains binder resins other than the fluororesin, the content of the other binder resins is preferably 80 mass% or less, more preferably 50 mass% or less, and even more preferably 20 mass% or less, based on the total amount of the fluororesin and the other binder resins.
[0056] In the resin composition, the mass ratio of the fluororesin to the CNTs (fluororesin / CNT) is preferably 0.1 or more, more preferably 0.5 or more. Also, it is preferably 10 or less, more preferably 5 or less. By setting it in the above range, the occurrence of aggregation and gelation can be suppressed, while the resistance and adhesion of the electrode film can be sufficiently obtained. More preferably, it is 0.1 to 10, and even more preferably 0.5 to 5.
[0057] The content of the non-aqueous dispersion medium in the resin composition is preferably 60% by mass or more, more preferably 65% by mass or more, and even more preferably 80% by mass or more, based on the mass of the resin composition (100% by mass). Also, it is preferably 99.5% by mass or less, more preferably 99% by mass or less, even more preferably 97% by mass or less, and even more preferably 95% by mass or less. By setting it in the above range, the occurrence of precipitation or gelation of CNTs and fluororesin can be suppressed, while the CNTs can be present better and more stably. It is more preferably 60% by mass or more and 99% by mass or less, and even more preferably 80% by mass or more and 95% by mass or less.
[0058] <Carbon nanotubes> Carbon nanotubes (CNTs) function as a conductive material. The resin composition may contain a conductive material other than carbon nanotubes. Examples of other conductive materials include carbon materials such as carbon black, graphene, multilayer graphene, and graphite. When using a conductive material other than CNTs, carbon black is preferred from the viewpoint of the adsorption performance of the dispersant, and examples of the carbon black include acetylene black, furnace black, and ketjen black. These carbon blacks may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black.
[0059] The CNT to be added to the resin composition has a cylindrical shape of planar graphite, and includes single-walled CNT and multi-walled CNT, and these may be mixed. Single-walled CNT has a structure in which one layer of graphite is wound, and multi-walled CNT has a structure in which two or three or more layers of graphite are wound. The sidewall of the CNT does not have to have a graphite structure. For example, CNTs having sidewalls with an amorphous structure are also CNTs in this specification. The CNT may be CNTs manufactured by any method. CNTs can generally be manufactured by laser ablation method, arc discharge method, thermal CVD method, plasma CVD method, and combustion method, but are not limited to these. The CNT may also be CNTs that have been surface-treated. The CNT may be a CNT derivative to which a functional group, such as a carboxyl group, has been added. CNTs that encapsulate organic compounds, metal atoms, or substances, such as fullerenes, may also be used.
[0060] The average outer diameter of the CNTs is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 15 nm or less. The average outer diameter of the CNTs can be calculated by first observing and photographing the CNTs with a transmission electron microscope, randomly selecting 300 CNTs from the observation photograph, and measuring the outer diameter of each of them.
[0061] The resin composition may be prepared by separately preparing two or more types of CNTs having different average outer diameters and adding them to a dispersion medium. When two or more types of CNTs having different average outer diameters are used as CNTs, the average outer diameter of the first CNT is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second CNT is preferably 5 nm or more and 20 nm or less. For example, single-walled carbon nanotubes may be used as the first CNTs, and multi-walled carbon nanotubes may be used as the second CNTs. When two or more types of CNTs having different average outer diameters are used as CNTs, the mass ratio of the first CNTs to the second CNTs is preferably 1:50 to 50:1, more preferably 1:10 to 10:1, and even more preferably 1:5 to 5:1. By setting the mass ratio of the first CNTs to the second CNTs in the above range, entanglement between the CNTs is suppressed, and a dispersion with excellent fluidity is obtained.
[0062] The average fiber length of the CNTs is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the CNTs can be calculated by first observing and photographing the CNTs with a scanning electron microscope, randomly selecting 300 CNTs from the photograph, and measuring the fiber length of each of them.
[0063] The aspect ratio is the value obtained by dividing the fiber length of the CNT by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. The higher the aspect ratio of the conductive material, the higher the conductivity that can be obtained when an electrode is formed. The aspect ratio of the CNT is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.
[0064] The specific surface area of CNT is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m2 / g or more is more preferable. 2 / g or less, and 2 / g or less is more preferable, and 2 / g or less is more preferable. The specific surface area of the CNT is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area are within the above ranges, a well-developed conductive path is easily formed in the electrode.
[0065] The carbon purity of CNT is expressed as the content (mass%) of carbon atoms in CNT. The carbon purity is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably 98 mass% or more, relative to 100 mass% of CNT. By keeping the carbon purity within the above range, it is possible to prevent problems such as short circuits caused by the formation of dendrites due to impurities such as metal catalysts. CNTs that have been subjected to a purification treatment for the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity may be used. The method of the purification treatment is not particularly limited, and any known method may be used.
[0066] The CNT to be added to the resin composition may be pretreated, and the pretreatment method may be a surface treatment using a chemical, a heat treatment, a pulverization treatment, or the like, but is not particularly limited thereto. Among them, pulverization is preferred. The pulverization may be either wet pulverization or dry pulverization, may be media pulverization, or may be pulverization without using media. In view of the ease of control of the physical properties of the CNT, dry pulverization is preferred, and further, it is preferred to combine dry pulverization and media pulverization. For example, examples of the pulverization device include a bead mill, a ball mill, and an attrition mill. The components to be put into the pulverization device may be only untreated CNT, but optional components such as a lubricant, a dispersant, and a surface treatment agent may be further added. Dry pulverization is preferred, but a liquid medium may be put into the pulverization device together with the untreated CNT if necessary. When a pulverization device is used, the pulverization may be any of the processing methods such as batch type, continuous dispersion, and circulation type dispersion, but in view of the ease of control of the physical properties of the CNT, a pulverization process using continuous dispersion is preferred. In the continuous dispersion pulverization process, the desired CNTs can be obtained by controlling the input mass per unit time of CNTs input into the pulverizer, the type, diameter, input amount, etc. of the pulverization media. In one example, the CNT raw material is continuously input into a continuous bead mill and then dry-pulverized. Although it varies depending on the scale and type of the pulverization device, for example, zirconia, alumina, iron, etc. are preferable as the media for pulverization. In addition, the media diameter is preferably 1 to 15 mm, more preferably 1 to 10 mm.
[0067] When CNTs are dispersed in a disperser by collision with media such as a bead mill, or when they are repeatedly passed through a disperser over a long period of time, the CNTs may be damaged and short-flak carbonaceous matter may be generated. When short-flak carbonaceous matter is generated, the viscosity of the resin composition decreases, and the gloss of the coating film obtained by coating and drying the resin composition increases, so judging only from these evaluation results, the dispersion state seems to be good. However, since short-flak carbonaceous matter has high contact resistance and is difficult to form a conductive network, the resin composition produced through such a dispersion process may deteriorate the resistance of the electrode. In addition, CNT dispersions containing short-flak carbonaceous matter are prone to the formation of CNT aggregates with the short-flak carbonaceous matter as nuclei, and the addition of fluororesin may cause poor dispersion. The degree to which short-flak carbonaceous matter is generated can be confirmed by diluting the dispersion, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, and drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.
[0068] <Dispersant> The resin composition contains a dispersant. The dispersant is preferably one that can stabilize the dispersion of CNTs in the resin composition. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption force to CNTs and provides good dispersion stability. Depending on the characteristics required for dispersing CNTs, a suitable type of dispersant can be used in a suitable amount.
[0069] As the resin-type dispersant, a (meth)acrylic polymer, a polymer derived from an ethylenically unsaturated hydrocarbon, a cellulose derivative, a copolymer thereof, or the like can be used.
[0070] Examples of the polymer derived from an ethylenically unsaturated hydrocarbon include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, nitrile rubbers, etc. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with aldehydes (acetoacetal-modified or butyral-modified, etc.), etc. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, JP 2019-087304 A, JP 2020-011934 A, and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, homopolymers of polyacrylonitrile, copolymers of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber. Polymers in which other substituents have been introduced into a portion of these polymers, modified polymers, etc. may also be used.
[0071] The weight average molecular weight of the resin type dispersant is preferably 500,000 or less, more preferably 300,000 or less, from the viewpoint of the affinity balance between the dispersed material and the dispersion medium, and from the viewpoint of resistance to the electrolyte. Also, it is preferably 3,000 or more, more preferably 5,000 or more. The resin type dispersant may be used alone or in combination of two or more kinds.
[0072] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), Denka Poval (polyvinyl alcohol resin manufactured by Denka Co., Ltd.), and J-Poval (polyvinyl alcohol resin manufactured by Nippon Acetate Poval Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Polyvinyl alcohols synthesized by known synthesis methods may also be used. Specific examples of commercially available polyvinylpyrrolidone resins include Luvitec K17 (K value: 15.0 to 19.0, low molecular weight), K30 (K value: 27.0 to 33.0), K90 (K value: 88.0 to 92.0), K90HM (K value: 92.0 to 96.0, high molecular weight) (manufactured by BASF Japan), K15, K30, K90, K120 (manufactured by ISP), polyvinylpyrrolidone K30 (K value: 27.0 to 33.0), K90 (K value: 88.0 to 96.0) (manufactured by Nippon Shokubai), PVP Examples of suitable polyvinylpyrrolidone include K12 (K value 10-14), K15 (K value 13-19), K30 (K26-K35), K60 (K value 50-62), and K90 (K value 88-100) (manufactured by DSP Gokei Food & Chemical Co., Ltd.). From the viewpoint of preventing an increase in viscosity, the polyvinylpyrrolidone preferably has a K value of 150 or less, more preferably a K value of 100 or less, and It is more preferable that the molecular weight is 85 or less. As commercially available nitrile rubbers, various grades having different nitrile ratios, hydrogenation rates, molecular weights, etc. are available under trade names such as Therban (hydrogenated nitrile rubber manufactured by ARANSEO), Baymod (nitrile rubber manufactured by ARANSEO), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and Nipole NBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by known synthesis methods may be used.
[0073] Surfactants may be used in place of or in addition to the resin-type dispersants described above. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.
[0074] <base> The resin composition may further contain a base. It is preferable that the resin composition contains a base, since it enhances the wettability of the CNTs in the dispersion medium, thereby improving the dispersibility, or improving the dispersion stability. The base to be added may be at least one selected from the group consisting of inorganic bases, inorganic metal salts, organic bases, and organic metal salts. The total amount of these is preferably 0.001 to 0.1 mass%, more preferably 0.005 to 0.05 mass%, based on the mass of the resin composition (100 mass%). If the amount of base added is too large, it may cause corrosion of the dispersion device and / or the inside of the battery. Here, the water content of the base to be added is preferably less than 5% by mass, more preferably less than 3% by mass, and even more preferably less than 2% by mass. If the base to be added contains a large amount of water, the adsorption of the dispersant to the dispersed material may decrease, and it may be difficult to make the dispersed material stably exist in the non-aqueous dispersion medium. By setting the water content within the above range, the problem of the resin composition gelling during storage can be prevented.
[0075] Examples of inorganic bases and inorganic metal salts include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, borates, and ammonium hydroxide of alkali metals or alkaline earth metals. Among these, hydroxides or alkoxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal possessed by the inorganic base may be a transition metal.
[0076] Examples of the organic base include primary, secondary and tertiary amine compounds having 1 to 40 carbon atoms (eg, alkylamines and amino alcohols) which may have a substituent, and organic hydroxides.
[0077] Examples of the primary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as propylamine, butylamine, isobutylamine, octylamine, 2-ethylhexylamine, and laurylamine; aminoalcohols such as 2-aminoethanol and 3-aminopropanol; and 3-ethoxypropylamine. Examples of the secondary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as dibutylamine, diisobutylamine, N-methylhexylamine, and dioctylamine, and aminoalcohols such as 2-methylaminoethanol. Examples of the tertiary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as triethylamine, tributylamine, N,N-dimethylbutylamine, N,N-diisopropylethylamine, dimethyloctylamine, trioctylamine, and dimethyldecylamine, triethanolamine, and 2-(dimethylamino)ethanol. The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethyl ammonium hydroxide, tetramethyl ammonium hydroxide, trimethyl phenyl ammonium hydroxide, 3-trifluoromethyl-phenyl trimethyl ammonium hydroxide, and benzyl trimethyl ammonium hydroxide. Among these, from the viewpoint of the action on CNTs, it is more preferable to use at least one selected from the group consisting of 2-aminoethanol, 3-aminopropanol, triethanolamine, and trimethyl-2-hydroxyethylammonium hydroxide.
[0078] Examples of organic metal salts include alkoxides of alkali metals and acetates of alkali metals. Examples of alkoxides of alkali metals include lithium methoxide, lithium ethoxide, lithium propoxide, lithium t-butoxide, lithium n-butoxide, sodium methoxide, sodium ethoxide, sodium propoxide, sodium t-butoxide, sodium n-butoxide, potassium methoxide, potassium ethoxide, potassium propoxide, potassium t-butoxide, and potassium n-butoxide. Among these, sodium t-butoxide is preferred from the viewpoint of easily supplying cations. The metal contained in the organic base may be a transition metal.
[0079] <Acid> The resin composition may further contain an acid. It is preferable to contain an acid in the resin composition, since it can suppress the polymerization of the fluororesin and the associated increase in viscosity and gelation of the composite slurry for the lithium ion battery positive electrode. The acid to be added may be either an inorganic acid or an organic acid. The total amount of these is preferably 0.001 to 1.0 mass%, more preferably 0.005 to 0.5 mass%, based on the mass of the resin composition (100 mass%). If the amount of acid added is too large, it may reduce the adsorption and dispersion ability of the dispersant to CNTs.
[0080] Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. Examples of organic acids include carboxylic acid compounds and sulfonic acid compounds. Examples of carboxylic acid compounds include formic acid, acetic acid, propionic acid, butyric acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, (meth)acrylic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, citraconic acid, and fluoroacetic acid. Examples of sulfonic acid compounds include methanesulfonic acid, paratoluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, and dinonylnaphthalenedisulfonic acid. In addition, anhydrides, hydrates, or acids in which a part of the above acids is a salt can also be used. These can be used alone or in combination of two or more.
[0081] <Binder resin> The binder resin is a resin used to bind substances together. The resin composition of the present invention contains a fluororesin as a binder resin. [Fluororesin] Fluorine resin is a resin containing fluorine, and has excellent heat resistance, chemical resistance, and adhesiveness, and functions as a binder resin. The fluororesin may have a structure in which hydrogen of polyethylene is replaced with fluorine or trifluoromethyl. Examples of the fluororesin include homopolymers such as polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), and polychlorotrifluoroethylene (PCTFE); and copolymers such as perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), and tetrafluoroethylene-perfluorodioxysol copolymer (TPE / PDD). These may be used alone or in combination of two or more.
[0082] Among fluororesins, polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), resins having these structural units, modified products thereof, or combinations thereof are preferred from the viewpoint of resistance. Among them, polyvinylidene fluoride-based resins are preferred, and examples thereof include homopolymers of polyvinylidene fluoride; copolymers of vinylidene fluoride with hexafluoropropylene, tetrafluoroethylene, and the like. Polyvinylidene fluoride-based resins may be modified, and for example, acidic groups such as carboxyl groups may be introduced. The fluororesins may be used alone or in combination of two or more.
[0083] The weight average molecular weight (Mw) of the fluororesin is preferably 100,000 or more, more preferably 300,000 or more, even more preferably 500,000 or more, and particularly preferably 750,000 or more. Also, it is preferably 5,000,000 or less, more preferably 2,000,000 or less. By setting the weight average molecular weight within the above range, it is possible to achieve both uniform dispersion of the fluororesin in the resin composition and adhesion of the electrode, which is preferable.
[0084] The weight average molecular weight is a weight average molecular weight converted into polystyrene equivalent, and can be measured by gel permeation chromatography (GPC). Specifically, it may be measured by the method described in the examples.
[0085] The glass transition point of the fluororesin is preferably 20° C. or lower, more preferably 10° C. or lower, and even more preferably 0° C. or lower, from the viewpoint of the film-forming property of the electrode film.
[0086] Commercially available polyvinylidene fluoride and its modified products include, for example, KF Polymer series manufactured by Kureha Corporation (W#7300, W#7200, W#1700, W#1300, W#1100, W#9700, W#9300, W#9100, L#7305, L#7208, L#1710, L#1320, L#1120) and the solef series manufactured by Solvay (6008, 6010, 6012, 1015, 6020, 5130, 9007, 460, 41308, 11010, 21510, 31508, 60512) (all trade names).
[0087] [Other resins] The resin composition may further contain other resins besides the fluororesin. Other resins are not particularly limited as long as they are usually used as binder resins for paints and the like, and can be appropriately selected according to the purpose. The binder resin used in the resin composition is preferably a resin capable of binding between substances such as active materials and CNTs. Examples of the binder resin used in the resin composition include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, and silicone resins; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used.
[0088] <Non-aqueous dispersion medium> The resin composition contains a non-aqueous dispersion medium as a dispersion medium. The non-aqueous dispersion medium is not particularly limited, but is preferably a high-dielectric constant solvent, and preferably contains a solvent consisting of any one of the high-dielectric constant solvents, or a mixed solvent consisting of two or more of them. In addition, the high-dielectric constant solvent may be used by mixing one or more other solvents.
[0089] Examples of high dielectric constant solvents include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), and others, such as tetrahydrofuran, urea, and acetonitrile. The relative dielectric constant of the high dielectric constant solvent can be a value described in a solvent handbook, etc., and is preferably 2.5 or more at 20°C. From the viewpoint of the solubility of the dispersant or binder resin, or the wettability of the CNT to the dispersion medium, the non-aqueous dispersion medium preferably contains an amide-based organic solvent, and more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The non-aqueous dispersion medium preferably contains 60% by mass or more of the amide-based organic solvent, and more preferably contains 80% by mass or more, based on the total mass of the non-aqueous dispersion medium. From the viewpoint of handling, it is even more preferable to use N-methyl-2-pyrrolidone alone.
[0090] <Optional ingredients> The resin composition may contain optional components such as other additives such as conductive materials other than carbon nanotubes, wetting agents, wetting penetrants, leveling agents, etc., as long as the object of the present invention is not hindered. The optional components can be added at any timing, such as before preparing the resin composition, during mixing, after mixing, or a combination thereof.
[0091] Since the resin composition contains optional components within a range that does not impede the object of the present invention and does not substantially contain active materials, the total content of carbon nanotubes, dispersant, and fluororesin in the resin composition is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the non-volatile components of the resin composition, i.e., the solid content of the resin composition (100% by mass). Also, it is sufficient that the total content is 100% by mass or less.
[0092] The conductive material other than the carbon nanotubes may include carbon black. The carbon black is preferably included in the resin composition within a range that does not impair the effects of the present invention. Based on the total of the carbon black and the carbon nanotubes, the carbon nanotube content is preferably 1 to 80 mass%, more preferably 1 to 50 mass%. Within these ranges, the dispersion state of the carbon nanotubes can be controlled, and high dispersibility and flowability can be better maintained in the state containing the fluororesin. Furthermore, the carbon black content is preferably 20 mass% or less, more preferably 15 mass% or less, based on the total mass of the resin composition.
[0093] An example of a method for producing a resin composition containing carbon black is a method of adding carbon black to a CNT dispersion in a method of adding a binder resin to a CNT dispersion described later. The stage of adding carbon black to a CNT dispersion is not particularly limited, and may be before, after, or simultaneously with the addition of carbon nanotubes, or a combination thereof. Another example of a method for producing a resin composition containing carbon black is a method of adding carbon black before, after, or simultaneously with the addition of a binder resin to a CNT dispersion, or a combination thereof. In this method, it is preferable that carbon black is added in a state in which carbon nanotubes are dispersed in the CNT dispersion. Alternatively, a combination of these methods may be used. That is, carbon black may be further added before, after, or simultaneously with the addition of a binder resin to a CNT dispersion containing carbon black, or a combination thereof.
[0094] <Method of producing resin composition for secondary battery electrode> The method for producing the resin composition for secondary battery electrodes is not particularly limited, but for example, the composition can be produced by preparing a CNT dispersion containing CNTs, a dispersant, and a non-aqueous dispersion medium, and then adding and mixing a fluororesin. That is, it is preferable to include the following steps. [Step I] Production of carbon nanotube dispersion liquid A step of producing a carbon nanotube dispersion liquid containing carbon nanotubes, a dispersant, and a non-aqueous dispersion medium. [Process II] A step of adding a fluororesin to the carbon nanotube dispersion liquid.
[0095] [Process I] Step I is a step of producing a carbon nanotube dispersion liquid. The method of preparing the CNT dispersion is not particularly limited, and examples thereof include a method of mixing CNT, a dispersant, and a dispersion medium all at once or in portions, and dispersing the mixture; a method of adding CNT, a dispersant, and, if necessary, a dispersion medium, wet-treating the CNT, and then adding the dispersion medium to prepare a dispersion; a method of mixing a dispersant and a dispersion medium to prepare a dispersant solution, and then adding and dispersing the CNT. In any of the methods, the dispersion treatment of the CNT is not particularly limited, but it is preferable to use various dispersion devices. The dispersion treatment can be performed in two or more stages by arbitrarily adjusting the timing of addition of the materials to be used. By sufficiently increasing the dispersibility of the CNT dispersion before adding the fluororesin, it is possible to prevent the fluidity and dispersibility of the resin composition from decreasing when the fluororesin is added.
[0096] An example of a CNT dispersion is described below. The resin composition having the above-mentioned components and properties is not limited to one produced using a CNT dispersion. The CNT dispersion contains CNT, a dispersant, and a dispersion medium, and may contain optional components as appropriate within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination of these. As the optional components, those described in the above resin composition can be used.
[0097] The CNT dispersion can be obtained by mixing and dispersing a composition containing CNTs, a dispersant, and a dispersion medium. The dispersion process of the CNT dispersion is preferably carried out until the particle size of the CNT dispersion becomes sufficiently small. For example, the volume-based median size (μm) of the CNT dispersion after the dispersion process, determined by a laser diffraction / scattering type particle size distribution analyzer, is preferably 40 μm or less, more preferably 35 μm or less.
[0098] The dispersion treatment of the CNT dispersion is preferably carried out until the viscosity of the CNT dispersion is sufficiently reduced. For example, the viscosity of the CNT dispersion after dispersion, measured at 25°C and 60 rpm using a B-type viscometer, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 5,000 mPa·s, even more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.
[0099] The content of CNT in the CNT dispersion is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and particularly preferably 2% by mass or more, based on the mass of the CNT dispersion (100% by mass). Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting it in the above range, the CNT can be well and stably present in the dispersion. More preferably, it is 2% by mass or more and 10% by mass or less. Also, it is preferable to appropriately adjust the content of CNT so that a CNT dispersion with appropriate fluidity or viscosity can be obtained depending on the specific surface area of CNT, affinity to the dispersion medium, dispersibility of the dispersant, etc.
[0100] Examples of the dispersing device used when dispersing the CNT dispersion include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, an attritor, a high shear mixer, a high pressure homogenizer, an ultrasonic homogenizer, and the like. Among them, in order to finely disperse the CNT in the CNT dispersion and obtain suitable dispersibility, it is preferable to use a high shear mixer, a high pressure homogenizer, an ultrasonic homogenizer, or a combination of these. In particular, from the viewpoint of promoting the wetting of the CNT and dissolving coarse particles, it is preferable to use a high shear mixer in the initial dispersion step, and then to use a high pressure homogenizer from the viewpoint of dispersing the CNT while maintaining its aspect ratio. The high pressure homogenizer can further increase the dispersibility of the CNT by performing the dispersion in multiple stages by circulation dispersion. In addition, by dispersing the CNT with the high pressure homogenizer and then dispersing it with a bead mill, the dispersion state can be made uniform while maintaining the fiber length. The pressure when using the high-pressure homogenizer is preferably 60 to 150 MPa, more preferably 60 to 120 MPa. The dispersing device used when dispersing the CNT dispersion may be equipped with a heat exchanger or a cooling liquid supply mechanism for cooling the CNT dispersion. By previously cooling the carbon nanotube dispersion or the crude dispersion that has become hot after dispersion, it is possible to suppress the generation of bubbles in the carbon nanotube dispersion, and also to suppress the remaining solid content on the wall of the dispersion tank or the like. The liquid temperature of the CNT dispersion is not particularly limited, but is preferably controlled to 25 to 75°C, more preferably 40 to 65°C.
[0101] Dispersion methods using a dispersion device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersion device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersion device body is equipped with a tank that supplies the dispersion liquid through piping and a tank that receives the dispersion liquid, and the dispersion liquid is passed through the dispersion device body. In addition, circulation dispersion is a method in which the dispersion liquid that has passed through the dispersion device body is returned to the tank that supplies the dispersion liquid, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is reached, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to uniformize the dispersion state compared to circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simple compared to pass dispersion. In the dispersion step, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of the conductive material proceed sequentially or simultaneously, and the final dispersion state differs depending on how the steps proceed, so it is preferable to control the dispersion state in each dispersion step by using various evaluation methods. For example, the dispersion state can be controlled by the method described in the Examples.
[0102] [Process II] Step II is a step of adding a fluororesin to the carbon nanotube dispersion liquid obtained in step I.
[0103] The resin composition is preferably obtained by adding a fluororesin to a CNT dispersion and mixing. The fluororesin may be used in a solution (varnish) state in which the fluororesin is dispersed or dissolved in a dispersion medium or the like, but is preferably used in a state that does not contain a dispersion medium, more preferably in a solid state, and particularly preferably in a powder state. By adding a powdered fluororesin to a CNT dispersion, the amount of the non-aqueous dispersion medium does not increase when the fluororesin is added, so that a resin composition having a high fluororesin concentration and a high non-volatile content concentration can be provided. Here, the form of the fluororesin is not particularly limited, and may be, for example, pellets, powder, granules, flakes, chunks, chopped fibers, or the like.
[0104] When fluororesin is added to a non-aqueous dispersion medium, the viscosity of the non-aqueous dispersion medium containing fluororesin increases in proportion to the amount of fluororesin added. When fluororesin is added to a CNT dispersion, the viscosity of the resin composition containing CNT and fluororesin is greatly affected not only by the viscosity of the fluororesin solution but also by the content and dispersion degree of CNT. In particular, when CNTs with long fiber length are uniformly and well dispersed while maintaining their length at a certain level or more in order to form a developed conductive network, and a fluororesin is added without destroying the conductive network to prepare a resin composition, the fluidity of the resin composition suddenly decreases when a certain concentration or more of fluororesin is added, and there is a risk of "twin powder" in which the fluororesin is clumped together. Once the "twin powder" is generated, it has a strong cohesive force and is difficult to dissolve in the resin composition containing CNT even if it is stirred for a long time using a stirring device. In addition, when shear stress is applied by a dispersion device, not only the "twin powder" is broken down, but also the adsorption of the dispersant that contributes to the dispersion of CNT is inhibited or the CNT is broken, which may result in the formation of a conductive network being difficult. A composite slurry produced in the presence of "split powder" has poor storage stability and may not be able to form a uniform electrode film. The resin composition of the present invention can achieve both the dispersibility of CNTs and the solubility of the fluororesin. Therefore, even when the fluororesin content is high, such as 3.1 mass% or more based on the mass of the resin composition, splicing of the fluororesin can be suppressed, resulting in a secondary battery with excellent electrical properties.
[0105] In step II, by controlling the rate at which the fluororesin is added (hereinafter referred to as the adding rate) and / or the temperature of the CNT dispersion, it is possible to prepare a uniform resin composition and to produce a composite slurry and an electrode film while maintaining good dispersibility of the CNTs. The above effect can be obtained by setting either the adding rate of the fluororesin or the temperature of the CNT dispersion when the fluororesin is added within an appropriate range, but it is more preferable to control both the adding rate and the liquid temperature. If the fluororesin is added without controlling the adding rate of the fluororesin and the temperature of the CNT dispersion, the fluidity of the resin composition may suddenly decrease, and there is a risk of "splicing" of the fluororesin clumped together.
[0106] The temperature of the CNT dispersion liquid can be 55°C or more and 80°C or less, and more preferably 60°C or more and 75°C or less, during at least one of the steps of adding and dissolving the fluororesin. This allows the fluororesin to dissolve sufficiently in the non-aqueous dispersion medium, so that it can be dissolved without being in a "powdered" state. In addition, by keeping the liquid temperature within the above range, it is possible to control the resin composition so that formula (I) or formula (I) and formula (II) satisfy specific conditions, and a resin composition with better dispersion stability can be obtained.
[0107] The liquid temperature of the CNT dispersion from the start of the addition of the fluororesin to the determination of the dissolution end point can be adjusted to be within the above range by heating or cooling the dispersion tank temperature, or by utilizing the shear heat generated by high-speed stirring using a homogenizer, disperser mixer, etc. More specifically, the liquid temperature is measured from the start of the addition of the fluororesin to the determination of the dissolution end point, and it is sufficient that the liquid temperature of the CNT dispersion reaches 55°C or more and 80°C or less within that addition / dissolution time.
[0108] The injection rate of the fluororesin into the CNT dispersion liquid can be 2.0 parts by mass / min or less, more preferably 1.0 parts by mass / min or less, and particularly preferably 0.5 parts by mass / min or less, relative to 100 parts by mass of the non-aqueous dispersion medium contained in the CNT dispersion liquid. The injection rate of the fluororesin into the CNT dispersion liquid is preferably 0.01 parts by mass / min or more, more preferably 0.03 parts by mass / min or more, relative to 100 parts by mass of the non-aqueous dispersion medium contained in the CNT dispersion liquid. By setting the injection rate as above, it is possible to add the fluororesin without agglomerating even if the fluororesin is dispersed in the non-aqueous dispersion medium at a high concentration, which is preferable.
[0109] Therefore, even if the content of the fluororesin is as high as 3.1 mass% or more based on the mass of the resin composition, the resin composition can be prepared without agglomerating the fluororesin. When the fluororesin is added at a rate higher than the above range, a higher shear force is required for the resin composition in order to uniformly mix and dissolve the fluororesin without agglomerating, which may result in the dispersion state of the CNT dispersion liquid prepared earlier being destroyed. The injection rate of the fluororesin into the CNT dispersion was 1 m per 1 m of reaction vessel volume. 3 Preferably, the flow rate is within the range of 0.5 kg / min to 10 kg / min, and more preferably within the range of 1 kg / min to 7.5 kg / min.
[0110] Furthermore, the amount of the fluororesin added to the CNT dispersion may be 3 parts by mass or more, 3.3 parts by mass or more, or 4 parts by mass or more, relative to 100 parts by mass of the non-aqueous dispersion medium contained in the CNT dispersion. The amount of the fluororesin added to the CNT dispersion is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the non-aqueous dispersion medium contained in the CNT dispersion. By having the content of the fluororesin within the above range, the entire amount of the fluororesin is easily dissolved in the resin composition, and the occurrence of aggregation and gelation can be suppressed, and the deterioration of the capacity characteristics of the battery can be prevented, which is preferable. In this way, when formula (I) or formula (II) satisfies the specific conditions, the resin composition for secondary battery electrodes of the present invention can have excellent dispersibility and stability over time even when the content of the fluororesin in the resin composition is high.
[0111] The method of adding the fluororesin to the CNT dispersion is not particularly limited, but it is preferable to add the fluororesin while stirring the CNT dispersion using a stirring device. The stirring device is not particularly limited, and mixers such as a disperser, homomixer, ultramixer, and planetary mixer can be used. When using a disperser (stirring blade), the shape is not particularly limited as long as it can homogeneously stir the resin composition, and there are various types such as a propeller type and a turbine type. In addition, the stirring speed can be appropriately adjusted depending on the size and rotation speed of the stirring blade. The stirring speed is not particularly limited as long as it is within the range allowed in the actual operation process, but a peripheral speed of 2.0 m / s or more is preferable, and a peripheral speed of 5.0 m / s or more is more preferable.
[0112] In addition, the method of dissolving the fluororesin in the CNT dispersion is not particularly limited, but it is preferable to dissolve the fluororesin using a mixer. Examples of the type of mixer include, but are not limited to, a disperser, a homomixer, an ultramixer, and a planetary mixer. In addition, it is preferable to use two or more types of mixers, such as a disperser suitable for circulating the bulk dispersion and a homomixer capable of applying high shear force. The shear rate of the mixer is not particularly limited, but the maximum shear rate is preferably 10,000 / sec or more, more preferably 50,000 / sec or more. By having the maximum shear rate in the above range, the splices, which are undissolved fluororesin, can be broken down by shear force to obtain a resin composition in which the fluororesin is dissolved uniformly. In addition, the maximum shear rate is preferably 150,000 / sec or less, more preferably 100,000 / sec or less. By having the maximum shear rate in the above range, the resin can be dissolved uniformly without destroying the dispersion state of the CNT.
[0113] <Secondary battery electrode composite slurry> The secondary battery electrode composite material slurry contains an active material in addition to the resin composition of the present invention. The resin composition of the present invention has a finely controlled dispersion state of CNTs and a dissolved state of the fluororesin, which is a binder resin, and is highly stable, so that the dispersibility and fluidity of the resin composition are maintained even after many days have passed. Even when the CNT concentration is higher than a certain level or the fluororesin content is high, it is possible to provide a secondary battery electrode composite slurry in which the dispersibility of CNTs is maintained even after mixing with an active material.
[0114] The composite slurry may contain other optional components as necessary within a range that does not impair the object of the present invention. The optional components may be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination thereof. The optional components may be those described in the above resin composition.
[0115] The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material". An active material is a material that is the basis of a battery reaction. Active materials are divided into positive electrode active materials and negative electrode active materials based on electromotive force. The composite slurry is preferably in a slurry state in order to improve uniformity and processability.
[0116] <Cathode active material> The positive electrode active material is not particularly limited. For example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used. For example, lithium manganese composite oxides (e.g., Li x Mn2O4 or LixMnO2), lithium nickel composite oxides (e.g. Li x NiO2), lithium cobalt complex oxide (Li x CoO2), lithium nickel cobalt complex oxide (e.g. Li x Ni 1-y Co y O2), lithium manganese cobalt complex oxide (e.g. Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (e.g. Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g. Li x Mn 2-y Ni y O4), lithium phosphate powder with an olivine structure (e.g. Li x FePO4, Li x Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (e.g. V2O5, V6O 13) Examples include transition metal oxide powders such as titanium oxide, transition metal sulfide powders such as iron(III) sulfate (Fe2(SO4)3), TiS2, and FeS. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These cathode active materials can be used alone or in combination of one or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to become highly basic due to elution of components derived from raw materials or metal ions, and as a result, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.
[0117] <Negative electrode active material> The negative electrode active material is not particularly limited. For example, it can be metal Li capable of reversibly doping or intercalating lithium ions, or an alloy thereof, a tin alloy, a silicon alloy negative electrode, Li X TiO2, Li X Fe2O3, Li X Fe3O4, Li X Metal oxide systems such as WO2, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number, where 0 < x < 1. These negative electrode active materials can be used alone or in combination of one or more. In particular, when using a silicon alloy negative electrode, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials.
[0118] The content of CNT in the composite slurry is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the active material. Also, it is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. If it exceeds the above range, the amount of the active material filled in the electrode may decrease, leading to a decrease in the capacity of the battery. Also, if it is below the above range, the conductivity of the electrode and the battery may be insufficient.
[0119] The content of the dispersant in the composite slurry is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the active material.
[0120] The content of the fluororesin in the composite slurry is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the active material. When the composite slurry contains other binder resins, the content of the other binder resins is preferably 80 mass% or less, more preferably 50 mass% or less, and even more preferably 20 mass% or less, based on the total of the fluororesin and other binder resins (100 mass%).
[0121] The non-volatile content in the composite slurry is preferably 40% by mass or more, more preferably 50% by mass or more, based on the mass of the composite slurry (100% by mass), and is preferably 90% by mass or less, more preferably 85% by mass or less.
[0122] As a method for preparing the composite slurry, a method of further adding an active material to a resin composition and stirring the mixture is preferred. The stirring device used for stirring is not particularly limited. A disperser, a homogenizer, etc. can be used as the stirring device.
[0123] The composite slurry may further contain carbon black, which functions as a conductive material. The carbon black is preferably contained in the composite slurry within a range that does not impair the effects of the present invention, and the carbon nanotubes are preferably contained in an amount of 1 to 80 mass%, more preferably 1 to 50 mass%, based on the total amount of the carbon black and the carbon nanotubes. Within these ranges, the dispersion state of the carbon nanotubes can be controlled, and high dispersibility and flowability can be better maintained in a state containing the fluororesin. Furthermore, the carbon black is preferably contained in an amount of 10 mass% or less, more preferably 5 mass% or less, based on the total mass of the composite slurry.
[0124] The method for producing the composite slurry includes a step of adding an active material to the resin composition, and may further include adding carbon black before, after, or simultaneously with the addition of the active material to the resin composition, or a combination thereof. Alternatively, the active material may be added to a resin composition that already contains carbon black, or the active material and carbon black may be further added to a resin composition that already contains carbon black.
[0125] ≪Electrode film≫ The electrode film is formed by forming the composite slurry into a film shape, and includes carbon nanotubes, a dispersant, a fluororesin, and an active material. The electrode film may further include an optional component. The electrode film can be obtained by adding an active material to the above-mentioned resin composition to prepare a composite slurry, and applying the composite slurry. For example, the electrode film can be formed by applying the composite slurry to a current collector and removing volatiles.
[0126] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.
[0127] The method of applying the composite slurry onto the current collector is not particularly limited, and any known method can be used. Specifically, die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, electrostatic painting, etc. can be mentioned. As a drying method after application, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, etc. can be used, but are not particularly limited thereto. In addition, after application of the composite slurry, a rolling process may be performed using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.
[0128] ≪Secondary battery≫ The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode has the above-mentioned electrode film. In the method for producing the secondary battery, for example, at least one of the positive electrode and the negative electrode is produced by applying a composite slurry to a current collector to form an electrode film, and the composite slurry is produced by adding an active material to the above-mentioned resin composition.
[0129] The positive electrode may be prepared by coating a composite slurry containing a positive electrode active material on a current collector and drying the mixture to prepare an electrode film. The negative electrode may be prepared by coating a composite slurry containing a negative electrode active material on a current collector and drying the mixture to prepare an electrode film. The positive electrode active material and the negative electrode active material may be the above-mentioned materials. The composite slurry may be prepared according to the above-mentioned method.
[0130] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous dispersion medium.
[0131] As the electrolyte salt, various conventionally known ones in which ions can move can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be mentioned, but are not limited thereto. It is preferable to dissolve the electrolyte salt in a non-aqueous dispersion medium and use it as an electrolyte solution.
[0132] The non-aqueous dispersion medium is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0133] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.
[0134] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes such as a paper type, a cylindrical type, a button type, a laminated type, etc., depending on the purpose of use. EXAMPLES
[0135] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". The blend amounts in the table are in parts by mass, and amounts other than the solvent are calculated as non-volatile contents. Note that blanks in the table indicate that no blend was made. The weight average molecular weight (Mw) of the fluororesin was measured by the following method.
[0136] <Measurement of weight average molecular weight (Mw) of fluororesin> The weight average molecular weight (Mw) of the fluororesin was measured using a gel permeation chromatography (GPC-900 manufactured by JASCO Corporation, Shodex KD-806M column, temperature 40°C) for an NMP solution in which the fluororesin powder was dissolved at 0.1 mass%, and the polystyrene equivalent value was calculated as the weight average molecular weight.
[0137] <Carbon nanotube high purification treatment> (Production Example 1: Production of 100T-P) 5g of water was added to 1g of carbon nanotubes (K-Nanos 100T: manufactured by Kumho Petrochemical), and the mixture was stirred with a Henschel-type mixer to obtain granular carbon nanotubes (particle size approximately 7mm). The granular carbon nanotubes were spread on a tray and dried for 7 hours in a reduced pressure hot air oven at 100°C to obtain compressed CNTs. The obtained compressed CNTs were placed in a ceramic crucible and placed in a firing furnace. The furnace was evacuated to a vacuum of 1 Torr or less, and then heated to 1000°C. Carbon tetrachloride gas was introduced at 0.3L per minute until the pressure in the furnace reached 90 Torr, and then the temperature in the furnace was raised to 1600°C and maintained for 1 hour. Next, the heater was stopped, and the pressure was slowly reduced to 1 Torr, and the mixture was allowed to cool to room temperature. The reduced pressure in the furnace was released, and the highly purified carbon nanotubes (100T-P) were collected from the crucible.
[0138] <Dry grinding process of carbon nanotubes> (Production Example 2: Production of BT1001M-C) In a dynamic mill (manufactured by Nippon Coke Co., Ltd.), zirconia beads with a diameter of 8 mm were charged as the grinding media, and carbon nanotubes (LUCAN BT1001M: manufactured by LG chem Ltd.) were fed at an operating condition of 100 kg / h and processed at a peripheral speed of 4.0 m / s, and the dry-ground carbon nanotubes (BT1001M-C) were collected.
[0139] <Production of Dispersant> (Production Example 3: Production of H-NBR3) In a stainless steel polymerization reactor, 32 parts of acrylonitrile, 68 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.48 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Next, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through it for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3MPa, and hydrogenation reaction was carried out for 6 hours. After that, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solids were dried to obtain a dispersant (H-NBR3). The Mooney viscosity (ML1+4, 100°C) of H-NBR3 (measured using an L-shaped rotor at a temperature of 100°C in accordance with Japanese Industrial Standard JIS K6300-1) was 44. The hydrogenation rate (calculated from infrared spectroscopy by total reflection measurement method) was 0.7%. The structural unit derived from acrylonitrile determined from the 1H-NMR quantitative spectrum was 32%.
[0140] The materials used in the examples and comparative examples are described below. <Carbon nanotubes> ·100T: K-Nanos 100T (manufactured by Kumho Petrochemical, multilayer CNT, average outer diameter 13 nm, specific surface area 210 m 2 / g) 100T-P: CNT produced according to Production Example 1 ·BT1001M:LUCAN BT1001M (manufactured by LG chem Ltd, multilayer CNT, average outer diameter 13nm, specific surface area 250m 2 / g) BT1001M-C: CNT produced according to Production Example 2 ·10B: JENOTUBE10B (manufactured by JEIO, multilayer CNT, average outer diameter 10 nm, specific surface area 230 m 2 / g) ·6A:JENOTUBE6A (manufactured by JEIO, multilayer CNT, average outer diameter 6nm, specific surface area 700m 2 / g)
[0141] <Dispersant> H-NBR1: Therban(R)AT 3404 (ARLANXEO, hydrogenated acrylonitrile-butadiene rubber) ·H-NBR2: Zetpole 2000L (manufactured by Zeon Corporation, hydrogenated acrylonitrile-butadiene rubber) H-NBR3: Dispersant produced according to Production Example 3 PVB: BL-10 (Sekisui Chemical Co., Ltd., polyvinyl butyral) PVP: K-30 (ISP, polyvinylpyrrolidone) PVA: Kuraray Poval 3-86SD (Kuraray, modified polyvinyl alcohol)
[0142] <Fluororesin> W#7300: KF Polymer W#7300 (Kureha, polyvinylidene fluoride resin, Mw: 1 million) S-5130: Solef5130 (Solvay, polyvinylidene fluoride resin, Mw: 1.1 million) W#1100: KF Polymer W#1100 (Kureha, polyvinylidene fluoride resin, Mw: 280,000) W#7200: KF Polymer W#7200 (Kureha, polyvinylidene fluoride resin, Mw: 630,000) W#9300: KF Polymer W#9300 (Kureha, polyvinylidene fluoride resin, Mw: 1 million) W#9700: KF Polymer W#9700 (Kureha, polyvinylidene fluoride resin, Mw: 880,000)
[0143] <Other ingredients; bases or acids> NaOH: Sodium hydroxide (Tokyo Chemical Industry Co., Ltd., purity >98.0%, granular) t-BuONa: Sodium t-butoxide (Tokyo Chemical Industry Co., Ltd., purity >98.0%) Aminoethanol: 2-aminoethanol (Tokyo Chemical Industry Co., Ltd., purity >99.0%) Succinic acid: Succinic acid (manufactured by Fujifilm Wako Pure Chemical Industries, purity >99.5%)
[0144] <Preparation of Resin Composition> (Example 1-1) [Process I] According to the materials and compositions shown in Table 1, the materials except for the acid and fluororesin were added in order to prepare a CNT dispersion liquid as follows. First, NMP was placed in a stainless steel jacketed tank and heated to 50°C. After adding a dispersant (H-NBR1) and a base (NaOH) while stirring with a disperser, the mixture was stirred for 1 hour to dissolve the dispersant (H-NBR1). Next, CNT (100T) was added while stirring with a disperser, and a square hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON) and batch dispersion was performed for 5 minutes at a speed of 8,000 rpm. The above CNT addition and dispersion process was repeated four times to add the entire amount of CNT, and the whole was uniform, and batch dispersion was performed with a high shear mixer until the dispersion particle size was 250 μm or less as measured by a grind gauge with a maximum groove depth of 300 μm. Next, the liquid to be dispersed was supplied from the jacketed tank to a high pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) via piping, and a pass-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, with 15 passes to obtain a CNT dispersion. The viscosity of the dispersion liquid at 60 rpm, measured with a B-type viscometer (TOKI SANGYO, VISCOMETER, MODEL: BL), was 800 mPa s.
[0145] [Process II] Next, the CNT dispersion was placed in a stainless steel jacketed tank, and the temperature of the jacketed tank was heated to 60°C so that the liquid temperature measured by a thermocouple thermometer was 60°C. While stirring with a disperser, 3.32 parts by mass of fluororesin (W#7300) was added in total at a rate of 0.8 parts by mass / min to 100 parts by mass of NMP in the CNT dispersion. The temperature was adjusted to maintain the liquid temperature of 60°C measured by the thermocouple thermometer, and the mixture was stirred for 3 hours using a homomixer (homogenizer MARKII, manufactured by PRIMIX) and a disperser to dissolve the entire amount of the fluororesin, thereby obtaining a resin composition 1. The maximum shear rate at this time was 60,000 / sec, and the liquid temperature measured by a thermocouple thermometer was 60±5°C.
[0146] (Examples 1-2 to 1-23) Resin compositions 2 to 23 were obtained in the same manner as in Example 1-1, except that the materials, compositions, and production conditions were changed according to those shown in Table 1.
[0147] (Examples 1-24) A resin composition was obtained in the same manner as in Example 1-1, except that the materials, composition, and production conditions were changed according to those shown in Table 1. The obtained resin composition was allowed to cool until the liquid temperature became 30° C. or less, and an acid (succinic acid) was added and stirred for 30 minutes with a disperser set at a peripheral speed of 12 m / sec, thereby obtaining resin composition 24.
[0148] (Examples 1-25) Resin composition 25 was obtained in the same manner as in Example 1-1, except that after adding the fluororesin, the mixture was stirred for 3 hours using a homomixer (Homomixer MARKII, manufactured by PRIMIX) and a disper, and the maximum shear rate was 100,000 / sec.
[0149] (Examples 1-26) Resin composition 26 was obtained in the same manner as in Example 1-1, except that after adding the fluororesin, the mixture was stirred for 3 hours using a homomixer (Homomixer MARKII, manufactured by PRIMIX) and a disper, and the maximum shear rate was 20,000 / sec.
[0150] (Examples 1-27 to 29) Resin compositions 27 to 29 were obtained in the same manner as in Example 1-1, except that the feeding rate and liquid temperature were changed as shown in Table 1.
[0151] (Comparative Example 1-1) Comparative resin composition 1 was obtained in the same manner as in Example 1-1, except that, according to the materials and composition shown in Table 1, the fluororesin was added at a rate of 3.32 parts by mass / min to 100 parts by mass of NMP in the CNT dispersion, and the conditions for dissolving the fluororesin were a liquid temperature of 25°C, stirring for 1 hour, and a maximum shear rate of 2,000 / sec. The liquid temperature measured with a thermocouple thermometer was 25±3°C.
[0152] (Comparative Example 1-2) Comparative resin composition 2 was obtained in the same manner as in Example 1-1, except that the fluororesin was added at a rate of 3.32 parts by mass / min to 100 parts by mass of NMP in the CNT dispersion, and the condition for dissolving the fluororesin was a liquid temperature of 45° C., according to the materials and composition shown in Table 1. The liquid temperature measured with a thermocouple thermometer was 45±5° C.
[0153] (Comparative Example 1-3) Comparative resin composition 3 was obtained in the same manner as in Example 1-1, except that the fluororesin was added at a rate of 3.32 parts by mass / min to 100 parts by mass of NMP in the CNT dispersion, and the fluororesin was dissolved under stirring for 6 hours at a liquid temperature of 35° C., according to the materials and composition shown in Table 1. The liquid temperature measured with a thermocouple thermometer was 35±5° C.
[0154] (Comparative Examples 1-4) [Process I] According to the materials and compositions shown in Table 1, the materials except for the fluororesin were added in order to prepare a CNT dispersion liquid in the same manner as in Example 1-1. [Process II] Next, the CNT dispersion was placed in a stainless steel jacketed tank, and the temperature of the jacketed tank was heated to 50°C so that the liquid temperature measured by a thermocouple thermometer was 50°C. While stirring with a disperser, 3.32 parts by mass of fluororesin (W#7300) was added little by little while visually checking (the addition rate was 2.2 parts by mass / min. relative to 100 parts by mass of NMP in the CNT dispersion). The temperature was adjusted to maintain the liquid temperature of 50°C measured by a thermocouple thermometer, and the binder resin was completely dissolved by stirring for 2 hours using a disperser, to obtain a comparative resin composition 4. The maximum shear rate at this time was 2,000 / sec, and the liquid temperature measured by a thermocouple thermometer was 49±3°C.
[0155] [Table 1-1]
[0156] [Table 1-2]
[0157] <Measurement and evaluation of physical properties of resin composition> The physical properties of the resin composition were measured and evaluated by the following methods. The results are shown in Tables 2 to 6. (Shear Viscosity of Resin Composition) Resin composition shear rate 1.0s -1 The viscosity at 25° C. was evaluated by performing flow curve measurement at a shear rate range of 0.01 to 1000 / sec using a rheometer (RheoStressl rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone diameter of 60 mm and 2°. The shear rate over time was evaluated by performing the above-mentioned flow curve measurement on the resin composition in a stationary state with the liquid temperature adjusted to 25° C.
[0158] (Complex Elastic Modulus of Resin Composition) The complex modulus of the resin composition was evaluated by performing dynamic viscoelasticity measurement at 25°C, a frequency of 1 Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStressl rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone of 60 mm diameter and 2°. The shear rate over time was evaluated by performing the above dynamic viscoelasticity measurement on the resin composition in a stationary state with the liquid temperature adjusted to 25°C.
[0159] Table 2 shows the shear viscosity η (Pa s) and complex modulus G * The measurement results in Pa are shown. For example, Table 2-1 shows the results of measurements using resin composition 1 obtained in Example 1-1 on the day of manufacture, resin composition 1 after static storage at 25°C for 7, 14, or 21 days, resin composition 1 after static storage at 40°C for 7, 14, or 21 days, and resin composition 1 after static storage at 60°C for 7, 14, or 21 days.
[0160] Tables 3 and 4 show the natural logarithm (ln(η)) of shear viscosity η (Pa s) and complex modulus G * The regression line was calculated using the least squares method from the scatter diagram plotting (Pa), and the coefficient of determination R 2 , slope a, and y-intercept b are recorded.
[0161] For example, the condition <1-1> in Table 3 is a resin composition after static storage at 25°C for 7 days, 14 days, and 21 days, the condition <2-1> is a resin composition after static storage at 25°C for 14 days and a resin composition after static storage at 40°C for 7 days and 14 days, and the condition <3> is the coefficient of determination R obtained by calculating a regression line from the values measured using a resin composition after static storage at 25°C for 14 days, a resin composition after static storage at 40°C for 7 days and 14 days, and a resin composition after static storage at 60°C for 14 days. 2 I , slope a I , y-intercept b I It is.
[0162] In addition, for example, in Table 4, the resin composition on the day of manufacture and the condition <1-1> are the coefficients of determination R obtained by calculating regression lines from the values measured using the resin composition on the day of manufacture and the resin composition after static storage at 25°C for 7 days, 14 days, and 21 days. 2 II , slope a II , y-intercept b II It is.
[0163] FIG. 1 shows, as an example, the resin compositions of Examples 1-1, 1-4, 1-28, and Comparative Example 1-1 under the conditions <3> An example of a scatter plot is shown, plotting the results of measurements taken using a resin composition after static storage at 25°C for 14 days, a resin composition after static storage at 40°C for 7 days and 14 days, and a resin composition after static storage at 60°C for 14 days. For example, the coefficient of determination R obtained from the regression line for the resin composition of Example 1-1 2 I is 0.99, slope a I is 9.9, y-intercept b I is 4.7, Coefficient of determination R obtained from the regression line for the resin composition of Comparative Example 1-1 2 I is 0.53, slope a I is 63.3, y-intercept b I was -184.3.
[0164] The measurements were performed in the same manner as in Example 1-1, and the coefficient of determination R 2 I , slope a I , y-intercept b I The coefficient of determination R 2 II , slope a II , y-intercept b II showed.
[0165] The criteria for judgment in Tables 3 to 5 are as follows. [Determination coefficient R 2 Criteria] A: 0.95 or higher B: 0.90 or more and less than 0.95 C: 0.85 or more and less than 0.90 D: Less than 0.85 [Standard for slope a] A: 7 to 14 B: 5 or more but less than 7, or 14 or more but less than 15 C: 2 or more but less than 5, or 15 or more but less than 20 D: Less than 2 or 20 or more [y-intercept b standard] A: 0 or more and less than 6 B: -3 or more and less than 0, or 6 or more and less than 8 C: -5 or more but less than -3, or 8 or more but less than 10 D: Less than -5 or 10 or more
[0166] [Table 2-1]
[0167] [Table 2-2]
[0168] [Table 2-3]
[0169] [Table 2-4]
[0170] [Table 3]
[0171] [Table 4]
[0172] [Table 5-1]
[0173] [Table 5-2]
[0174] (filtration speed) The dispersibility of the resin composition was evaluated by the filtration rate. The filtration rate test was carried out by adding 160g of NMP to 40g of resin composition and mixing thoroughly by shaking. The entire amount was placed in a 300mL vacuum filtration filter holder, and a scale was placed under the receiving container in the suction filter to measure the weight versus the time it took to pass through a 10μm mesh. The shorter the time it took to filter the entire amount of diluted resin composition, the better the dispersibility. Also, poorly dispersed samples contained aggregated CNTs or undissolved fluororesin, and the entire amount could not be filtered. If the evaluation criterion was + or higher, it was possible to use the product. [Evaluation Criteria] +++: Less than 60 seconds ++ : 60 seconds or more but less than 120 seconds + : 120 seconds or more NG: The entire amount cannot be filtered.
[0175] (Storage stability) The storage stability was evaluated by measuring the initial viscosity of the resin composition and the viscosity after storing the resin composition at 40°C for 7 days, and calculating the rate of change in viscosity after storing the resin composition at 40°C for 7 days relative to the initial viscosity. The viscosity of the resin composition was measured using a B-type viscometer ("BL" manufactured by Toki Sangyo) at a temperature of 25°C by thoroughly stirring with a spatula and immediately thereafter at a rotor speed of 60 rpm. If the evaluation standard is + or higher, the resin composition is usable. [Evaluation Criteria] +++: Less than 200% ++ : 200% or more but less than 500% + : 500% or more but less than 1000% NG: 1000% or more (gelled)
[0176] [Table 6]
[0177] <Preparation of positive electrode mixture slurry and positive electrode> (Examples 2-1 to 2-33, Comparative Examples 2-1 to 2-4) According to the combinations and composition ratios shown in Table 7, positive electrode mixture slurries and positive electrodes were prepared as follows. Capacity 150cm 3 The resin composition and the positive electrode active material were added to the plastic container and stirred at 2,000 rpm for 5 minutes using a centrifugal mixer (Thinky, Awatori Rentaro, ARE-310) to obtain a positive electrode mixture slurry. The non-volatile content of the positive electrode mixture slurry was 78 mass%.
[0178] The positive electrode composite slurry was applied to an aluminum foil having a thickness of 20 μm using an applicator, and then heated and dried in an electric oven at 120±5° C. for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain positive electrodes (positive electrodes 1 to 33, comparative positive electrodes 1 to 4). The weight per unit area of the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.2 g / cc.
[0179] In the examples and comparative examples, the following positive electrode active materials were used. NMC1: CellSeed NMC (LiNi 0.6 Co 0.2 Mn 0.2 O2, manufactured by Nippon Chemical Industry Co., Ltd. ·NMC2:S800(LiNi 0.8 Mn 0.1 Co 0.1 O2, made by Kinwa) NCA: NAT-7050 (LiNi 0.8 Co 0.15 Al 0.05 O2, manufactured by BASF Toda Battery Materials) LFP: HED(TM) LFP-400 (lithium iron phosphate, manufactured by BASF) LFMP: LFMP64 (lithium magnesium iron phosphate, manufactured by Ronbay)
[0180] <Evaluation of the positive electrode> (Positive electrode conductivity) The surface resistivity (Ω / □) of the composite layer of the obtained positive electrode was measured using Mitsubishi Chemical Analytech's Loresta GP, MCP-T610. After measurement, the thickness of the composite layer was multiplied to obtain the volume resistivity (Ω·cm) of the positive electrode. The thickness of the composite layer was measured at three points in the electrode using a film thickness meter (NIKON, DIGIMICRO MH-15M), and the thickness of the aluminum foil was subtracted from the average value to obtain the volume resistivity (Ω·cm) of the positive electrode. The smaller the volume resistivity, the more desirable it is. [Evaluation Criteria] ++++: Less than 10 Ω cm +++: 10 Ω·cm or more and less than 20 Ω·cm ++: 20Ω·cm or more and less than 30Ω·cm + :30Ω·cm or more
[0181] (Adhesion of positive electrode) The obtained positive electrode was cut into two rectangles of 90 mm x 20 mm with the coating direction as the long axis. A tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho) was used to measure the peel strength, and it was evaluated by a 180-degree peel test method. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitto) of 100 mm x 30 mm size was attached to a stainless steel plate, and the composite layer side of the prepared positive electrode was attached to the other side of the double-sided tape to prepare a test sample. Next, the test sample was fixed vertically so that the short sides of the rectangle were at the top and bottom, and the end of the aluminum foil was peeled off while pulling it from the bottom to the top at a constant speed (50 mm / min), and the average value of the stress at this time was taken as the peel strength. The higher the peel strength, the more desirable it is. [Evaluation Criteria] ++++:0.8N / cm or more +++: 0.5N / cm or more and less than 0.8N / cm ++: 0.3N / cm or more and less than 0.5N / cm + : Less than 0.3N / cm
[0182] [Table 7]
[0183] <Preparation of secondary battery> (Preparation of standard negative electrode) 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka), 1 part of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500L, manufactured by Nippon Paper Industries, non-volatile content 100%), and 98.4 parts of water were added to a 150 ml plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). 97 parts by mass of artificial graphite (CGB-20, manufactured by Nippon Graphite Industries) was then added as an active material, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). Next, 3.1 parts of SBR (styrene butadiene rubber, TRD2001, non-volatile content 48%, manufactured by JSR) was added and stirred at 2,000 rpm for 30 seconds using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain a standard negative electrode composite slurry. The non-volatile content of the standard negative electrode composite slurry was set to 50 mass%.
[0184] The above-mentioned standard negative electrode composite slurry was applied to a 20 μm-thick copper foil current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of 10 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metals, 3 t hydraulic roll press) to prepare a standard negative electrode with a mixture layer density of 1.6 g / cm3.
[0185] (Examples 3-1 to 3-33, Comparative Examples 3-1 to 3-4) The positive and negative electrodes shown in Table 8 were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively, and the punched positive and negative electrodes and the separator (porous polypropylene film) inserted between them were inserted into an aluminum laminate bag and dried in an electric oven at 70 ° C. for 1 hour. Then, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte in which ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1, and 1 part by mass of vinylene carbonate was added to 100 parts by mass as an additive, and LiPF6 was dissolved at a concentration of 1 M) was injected, and the aluminum laminate was sealed to prepare secondary batteries.
[0186] <Battery evaluation> (Rate characteristics of secondary batteries) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 1mA (0.02C)) at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, constant current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 3V. After repeating this operation three times, constant current / constant voltage charging (cutoff current (1mA0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, and constant current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage reached 3.0V, and the discharge capacity was calculated for each. The rate characteristic can be expressed as the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) The higher the rate characteristic, the more desirable it is. [Evaluation Criteria] ++++:80% or more +++: 60% or more but less than 80% ++: 40% or more but less than 60% + : Less than 40%
[0187] (Cycle characteristics of secondary batteries) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 200 times. The cycle characteristics can be expressed as the ratio of the 3rd 0.5C discharge capacity at 25°C to the 200th 0.5C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic = 200th 0.5C discharge capacity / 3rd 0.5C discharge capacity ×100(%) Higher cycle characteristics are more desirable. [Evaluation Criteria] ++++:85% or more +++: 80% or more but less than 85% ++: 50% or more but less than 80% + : Less than 50%
[0188] [Table 8]
[0189] As shown in Tables 6 to 8, it was confirmed that the resin composition for secondary battery electrodes of the present invention has high filtration speed and storage stability, and has high dispersibility and fluidity. In addition, the composite slurry for secondary battery electrodes has good dispersibility of CNTs in a state containing active material, the electrode film using this has high conductivity and adhesion, and the obtained secondary battery has excellent rate characteristics and cycle characteristics. This confirmed that it is a high-output, high-capacity, long-life secondary battery. In this way, it was confirmed that even when the content of the fluororesin is a high concentration of 3.1 mass% or more based on the mass of the resin composition for secondary battery electrodes, the composition has high dispersibility and fluidity and can be suitably used for secondary battery electrodes.
[0190] Although the present invention has been described above with reference to the embodiment, the present invention is not limited to the above. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the invention.
Claims
1. The present invention includes carbon nanotubes, a dispersant, a fluororesin, and a non-aqueous dispersion medium, The coefficient of determination R of the regression line represented by the following formula (I) 2 I is 0.85 or more, and the slope a I is 2≦a I <20 and y-intercept b I is -5≦b I <10. The resin composition for a secondary battery electrode. y = ax I + b I ... Equation (I) (Formula (I) is is a regression line expressed by the least squares method from a scatter diagram in which x is plotted on the horizontal axis and y is plotted on the vertical axis, the measurement being performed using at least three of the resin compositions for secondary battery electrodes after static storage at T° C. for i days, x is 25° C., shear rate 1.0 s -1 Shear viscosity η T-i (Pa.s) Nature Logarithm (ln(η T-i )) and y is the complex modulus G at 25° C. and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa), i is the number of days that have passed since static storage, assuming that the production date of the resin composition for a secondary battery electrode is day 0, and is 7, 14, or 21; T is the static storage temperature of the resin composition for secondary battery electrodes, which is 25, 40, or 60.
2. The present invention includes carbon nanotubes, a dispersant, a fluororesin, and a non-aqueous dispersion medium, The coefficient of determination R of the regression line represented by the following formula (II) 2 II is 0.85 or more, and the slope a II is 2≦a II <20 and y-intercept b II is -5≦b II <10. The resin composition for a secondary battery electrode. y = a II x + b II ... Equation (II) (Formula (II) is is a regression line expressed by the least squares method from a scatter diagram plotting x on the horizontal axis and y on the vertical axis, the scatter diagram being obtained by measuring at least two of the resin composition for a secondary battery electrode on the day of manufacture and the resin composition for a secondary battery electrode after static storage at T° C. for i days; x is 25° C., shear rate 1.0 s -1 Shear viscosity η T-i (Pa s) natural logarithm (ln(η T-i )) and y is the complex modulus G at 25° C. and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement * T-i (Pa), i is the number of days that have passed since static storage, assuming that the production date of the resin composition for a secondary battery electrode is 0, and is any one of 7, 14, or 21; T is the static storage temperature of the resin composition for secondary battery electrodes, which is 25, 40, or 60.
3. After being stored at T° C. for i days, the resin composition for a secondary battery electrode is <1-1> Resin compositions for secondary battery electrodes after static storage at 25° C. for 7, 14, and 21 days; <1-2> A resin composition for a secondary battery electrode after static storage at 40° C. for 7, 14, and 21 days, or <1-3> Resin compositions for secondary battery electrodes after static storage at 60° C. for 7, 14, and 21 days; 3. The resin composition for a secondary battery electrode according to claim 1, wherein the resin composition is any one of the following:
4. After being stored at T° C. for i days, the resin composition for a secondary battery electrode is <2-1> T is 25 or 40, At least one of the resin compositions for secondary battery electrodes after static storage at 25° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, <2-2> T is 25 or 60, At least one of a resin composition for a secondary battery electrode after static storage at 25° C. for 7, 14, and 21 days, and at least one of a resin composition for a secondary battery electrode after static storage at 60° C. for 7, 14, and 21 days, or <2-3> T is 40 or 60, At least one of the resin compositions for secondary battery electrodes after static storage at 40° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 60° C. for 7, 14, and 21 days, 3. The resin composition for a secondary battery electrode according to claim 1, wherein the resin composition is any one of the following:
5. After being stored at T° C. for i days, the resin composition for a secondary battery electrode is <3> At least one of the resin compositions for secondary battery electrodes after static storage at 25 ° C. for 7, 14, and 21 days, at least one of the resin compositions for secondary battery electrodes after static storage at 40 ° C. for 7, 14, and 21 days, and at least one of the resin compositions for secondary battery electrodes after static storage at 60 ° C. for 7, 14, and 21 days, The resin composition for a secondary battery electrode according to claim 1 or 2.
6. 3. The resin composition for a secondary battery electrode according to claim 1, wherein the fluororesin has a weight average molecular weight of 100,000 or more and 2,000,000 or less.
7. A composite slurry comprising the resin composition for a secondary battery electrode according to claim 1 or 2 and an active material.
8. An electrode film formed from the composite slurry according to claim 7.
9. A secondary battery including a positive electrode and a negative electrode, A secondary battery, wherein at least one of a positive electrode and a negative electrode has the electrode film according to claim 8.
Citation Information
Patent Citations
Copolymer for energy device electrode and energy device using the same
JP2016143635A
Manufacturing method of cathode slurry for lithium ion secondary battery
JP2017174535A
Electrode binder resin
JP2018181486A
Carbon nanotube dispersion, composition for secondary battery electrodes using the same, electrode membrane, secondary battery
JP2021176140A
Electrode mixture
WO2013176093A1